A moment-vector approach to interoperable analysis. (September 2018) - Taber, Andrew; Kumar, Goldy; Freytag, Michael; Shapiro, Vadim
Abstract: We propose a moment-vector based approach to interoperable analysis that takes advantage of representation-specific optimizations while retaining broad applicability. The major bottleneck of interoperable analysis is volume integration, and moments provide an informationally complete means to ensure accurate integration of a large class of integrands. Moments can be computed directly and in parallel from a diverse set of geometric representations and have simple compositional properties. We demonstrate our moment-based analysis pipeline by analyzing a boundary mesh representation with defects, G-code representation of a 3D printed part, a procedural skeleton representation, and an image stack representation of a bone obtained from a CT scan. Graphical abstract: Highlights: A moment-vector based approach to interoperable analysis. Moments are robust and can be efficiently computed from a diverse set of representations. Demonstrated our approach by analyzing a variety of representations.